Parent perceptions of changes in eating behavior during COVID-19 of school-aged children from Supplemental Assistance Program Education (SNAP-Ed) eligible households in California - Suzanne Rauzon; Sridharshi C. Hewawitharana; Erin E. Esaryk; Hannah R. Thompson; Lauren Whetstone; Ingrid Cordon; Gail M. Woodward-Lopez (Preventive Medicine Reports, 2023)
This cross-sectional study examined the associations between parent-reported, perceptions of changes in school-aged children’s (ages 5–18) school meal participation, household cooking, fast food consumption, dietary intake, and weight during the COVID-19 pandemic. Respondents with low-income and school-aged children (n = 1040) were enrolled using quota sampling to approximate the distribution of low-income households and race/ethnicity among California residents who completed an on-line questionnaire developed by the authors. Adjusted multinomial models examined associations between parent-reported changes in school meal participation and time spent cooking, with parent-reported changes in child diet and body weight during COVID-19 (from before March 2020 to January-March 2021). During the pandemic, decreased school meal participation was associated with decreased child’s fast food intake (OR[95 %CI] = 1.47[1.04–2.07]); conversely, increased school meal participation was associated with increased child’s fast food intake (OR[95 %CI] = 1.71[1.09–2.68]). Decreased cooking at home was associated with decreased fruit and vegetable intake (OR[95 %CI] = 2.71[1.62–4.53]), increased sugar-sweetened beverage intake (OR[95 %CI] = 3.83[2.16–6.81]), and increased fast food intake (OR[95 %CI] = 4.09[2.45–6.84]); while increased cooking at home was associated with increased fruit and vegetable (OR[95 %CI] = 2.26[1.59–3.20]), sugar-sweetened beverage (OR[95 %CI] = 1.88[1.20–2.94]), sweets (OR[95 %CI] = 1.46[1.02–2.10]), and salty snack food intake (OR[95 %CI] = 1.87[1.29–2.71]). These parent-reported perceived changes in meal sources during the pandemic for children from low-income California households, and the mixed results in their associations with changes in parent-reported child dietary intake, suggest the need for strengthening policies and programs to support both access to, and healthfulness of, meals from school and home during prolonged school closures.